(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
Ammonites and belemnites from a Middle Jurassic section at Telma-Dareh (Alborz Mountains, northern Iran) are described. The lithology of the studied section consists of an alternation of marls and limestones attributed to the Dalichai Fm., overlying the top of the Shemshak Fm. (sandstones) and underlying the Lar Fm. (limestones). Fossils are rather abundant but concentrated in ten scattered levels, ranging from the Aalenian (Scissum-Murchisonae zones) up to the Bajocian. Ammonites (Tmetoceras scissum, Leioceras cf. comptum, Ludwigia cf. murchisonae, Onychoceras ? sp., and Leptosphinctes sp.), belemnites (Brevibelus breviformis, Holcobelus cf. munieri ) and bivalves are the most abundant and well-preserved fossils; accessory elements are scarce brachiopods and gastropods. The palaeobiogeographic affinities of the belemnite fauna is Subboreal-Submediterranean, whereas the ammonites have Submediterranean-Tethyan affinities. The Aalenian age of the lower part of the Dalichai Fm. at Telma-Dareh differs from the Bajocian age attributed by other authors to this formation in other localities.